Karakteristik Laju Pendinginan Dan Coefficient Of Performance (COP) KTE-2000EV Menggunakan Katup Ekspansi Otomatis Dan Katup Ekspansi Thermostatik - Budi Dharma (Rekayasa Material, Manufaktur dan Energi, 2018)
The purpose of the study was to determine the characteristics of the cooling rate and The ideal coefficient of performance (COP) is the KTE-2000 EV refrigeration machine using an automatic expansion valve and thermostatic expansion valves. Analysis of the cooling and COP rates is ideally done by measuring changes in room temperature and plotting data on temperature and compressor pressure on the suction side and press side (suction line and discharge line) in the P-h diagram for the type of refrigerant R-404a. The test results show the characteristics of the average KTE-2000 EV cooling rate using an automatic expansion valve is 0.035 oC / s with an ideal COP value between 1.91 to 2.02, while for the thermostatic expansion valve the cooling rate characteristics obtained are an average of 0.024 oC / s and the ideal COP value between 2.58 and 3.13.